Monolithic Additively Manufactured Conformal 4x4 MIMO Radar Frontend based on Slotted Waveguide Array Antennas for 77 GHz Corner Radar - Lomakin, Konstantin; Alhasson, Saif; Hofmann, Andreas; Sippel, Mark; Gold, Gerald (2023 IEEE Conference on Antenna Measurements and Applications (CAMA), 2023)
In this work, an additively manufactured MIMO radar antenna setup is presented based on stereolithography 3D-printing of photopolymer resin and subsequent electroplating. The 8 antennas are based on slotted waveguide array design, each with 20 radiating elements along the elevation plane and are combined with an additional horn aperture on top of the radiating elements. The array incorporates two types of antennas which differ within the horn aperture yielding one type with wide azimuthal field of view and the other with a narrow field of view.Moreover, the antenna elements are conformally placed on a bent surface, consequently, directing the maximum gain into different directions.The entire array is manufactured as one monolithic part without the need of tedious assembly steps and thus, enhancing the feasibility towards serial productio